2015
DOI: 10.1002/jmv.24100
|View full text |Cite
|
Sign up to set email alerts
|

IL28Brs12980275 polymorphism shows association with response to treatment in Pakistani patients with Chronic Hepatitis C

Abstract: The aim of this study was to describe the genetic characteristics of Pakistani patients infected with hepatitis C virus (HCV) in relation to IL28B polymorphisms and its association to interferon and ribavirin treatment response. A total of 220 patients, infected with HCV were enrolled, out of which 100 were responders and 120 were nonresponders. The whole blood samples were collected to extract viral RNA and genomic DNA. PCR following the restriction fragment length polymorphism method was used to genotype IL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The SVR rate was 59.7% in our study group, and it was associated significantly with favorable genotypes of the IL28B gene polymorphisms. Consistent to our findings were the results of the studies of Shaikh et al [25] and Domagalski et al [26]. The study of Shaikh et al included a cohort of 220 Caucasian (Pakistani) patients with chronic hepatitis C treated with PEGIFN/RBV [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SVR rate was 59.7% in our study group, and it was associated significantly with favorable genotypes of the IL28B gene polymorphisms. Consistent to our findings were the results of the studies of Shaikh et al [25] and Domagalski et al [26]. The study of Shaikh et al included a cohort of 220 Caucasian (Pakistani) patients with chronic hepatitis C treated with PEGIFN/RBV [25].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent to our findings were the results of the studies of Shaikh et al [25] and Domagalski et al [26]. The study of Shaikh et al included a cohort of 220 Caucasian (Pakistani) patients with chronic hepatitis C treated with PEGIFN/RBV [25]. The SVR rate was 45.5%, and there was a significant association between the SVR and IL28B gene polymorphisms.…”
Section: Discussionsupporting
confidence: 90%
“…Conclusions drawn by Shaikh et al were in contrast with the analysis in this study, which showed 3a (50.8%) as most prevalent, and exceptionally high frequency of untypable (47%) was observed, followed by 2a (1.6%). All other genotypes were not seen in a total of 120 sample size (68).…”
Section: Hcv Genotype Prevalence In Pakistan 409mentioning
confidence: 91%
“…While the Urdu speaking ethnic community has heterogeneous Indian ancestry [56]. Thus the genetic variations exhibit significant differences in the risk of developing various disorders and disease progression in the Pakistani population [15,57,58].. Majority of the preeclamptic patients in our study were Sindhi (56%) and Urdu (27.2%) speaking.…”
Section: Discussionmentioning
confidence: 84%
“…The common SNVs found in association with preeclampsia include F5: c.1601G > A (rs6025), MTHFR: c.665C > T (rs1801133), MTHFR: c.1286A > C (rs1801131), VEGFA: c.-2055A > C (rs699947) and VEGFA: c.*237C > T (rs3025039) [12][13][14]. The influence of the SNVs on disease outcome is variable among different world populations, possibly due to ethnic variations and the findings may not be generalized [15].…”
Section: Introductionmentioning
confidence: 99%